Pendampingan Manajemen Pakan dan Budi Daya Itik Pedaging Berbasis Integrated Farming di Kabupaten Blitar - lestari ningsih; Muhammad Yusuf Yasin; Muhammad Khoirul Abidin; Mad’ud Zakqi Hupron; Muhamad Muhsin; Husna Fikriya; Riska Mei Puspitasari; Qurrotul A’yun; Isna Nurul Fajriyah; Umril Mu’minin; Poppy Yuliana Putri (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
This Holistic Village Development and Empowerment Program (PHP2D) aims to increase the productivity of broiler duck farmers in Dayu Village, Nglebok District, Blitar Regency, covering the level of knowledge, skills and income. The disseminated system is an integrated farming system between livestock waste in the form of duck droppings and wood shavings as a medium for growing maggots. Furthermore, the cultivated maggot is processed and used as one of the feed ingredients for broiler ducks. This activity is carried out for 5 months in 2020. The method used is counseling, training and mentoring. The material provided consisted of maggot cultivation, broiler duck cultivation, making ration formulations, and implementing an integrated farming system between maggot and broiler ducks. Monitoring and evaluation is carried out through pretest before the activity and posttest after the activity. The data were tabulated using excel and analyzed using a qualitative descriptive approach. The results obtained are that there is a trend of increasing partner knowledge by 40%, increasing partner skills by 45%, and increasing partner income by 40%. Feed management and broiler duck farming activities based on integrated farming can increase the level of knowledge, skill level and income level of broiler duck farmers in Dayu Village, Nglegok District, Blitar Regency.